Recuperación de espacio público y áreas verdes en barrios consolidados de la ciudad de Riobamba caso de estudio: Parque 21 de abril (Loma de Quito) - Noboa Carrillo, Pedro Andrés (2023)
The 21 de Abril Park is one of the most unique spaces in Riobamba City. The park traces its history back to 1900. From its origin to the present time, the square has seen five interventions that have transformed this public space's morphology. Two of these interventions were large-scale, and three were of smaller scale. Because the interventions have impacted the park's architectural foundation, this study has assessed the urban-architectural and the use of the 21 de Abril Park. The assessment is based on analyzing some indicators which allowed the researcher to know the current state of this public space. Data collection included a matrix of seven indicators: security, comfort, accessibility, landscaping, infrastructure, activity, and users. The results suggest a low influx of people explained by unsustainable interventions over time. The study also indicates a regular infrastructure state and little offer of recreational activities that limit the users' frequency and time of visits. This research also determined that the park's location within the residential and commercial area with historical value requires a proposal to equip it according to national and international guidelines. Adopting strategies to generate activities and reduce social problems is necessary to make 21 de Abril Park an attractive place for tourism to enhance the quality of this public space, ultimately allowing for this area's socioeconomic development.